The association of type D personality and premenstruel syndrome - Yıldırım Baş, Funda; Tola, Esra Nur; Çankaya, Başak Aslı (Süleyman Demirel University, 2022)
Objective Type D personality, defined as the presence of two personality characters -negative affectivity (NA) and social inhibition (SI), is associated with various disorders. The aim of our study was to investigate the association between Type D personality and premenstruel syndrome (PMS). Material and Methods A total of 286 female (86 with PMS and 200 control) were recruited for the study. The mean age of the participants was 21.28 ± 0.12 years. Data were obtained from the Premenstrual Syndrome Scale, Beck Depression Inventory (BDI-21) and Type D Personality Scale (DS14). SPSS 22 (Statistical Package for Social Sciences) program was used to evaluate the data. Statistical significance level was accepted as p<0.05. T test was used to compare continuous variables, chi-square test was used to compare categorical data, and pearson correlation test was used to determine the relationships between continuous variables. Results Depression and Type D personality were found to be significantly more common in the PMS group than in the control group (p<0.0001). Type D personality was positively correlation with PMS and BDI-21 (r=0.434, p<0.0001; OD (r=0.621, p<0.0001). Conclusion A positive relationship was found between PMS and depression and Type D personality. Prospective studies with a large number of patients are needed to better understand the underlying mechanisms.

Amaç Negatif duygulanım ve Sosyal içe dönüklük olmak üzere iki kişilik karakterinin varlığı olarak tanımlanan D tipi kişiliğin, çeşitli hastalıklarla ilişkili olduğu bilinmektedir. Çalışmamızın amacı, Tip D kişilik ile premenstruel sendrom (PMS) arasındaki ilişkiyi araştırmaktır. Gereç ve Yöntem Çalışmaya toplam 286 kadın (PMS:86; kontrol:200) dahil edildi. Yaş ortalamaları 21,28 ± 0,12 di. Veriler Premenstrüel Sendrom Ölçeği, Beck Depresyon Envanteri (BDI-21), D Tipi kişilik Ölçeği (DS14) sonuçlarından elde edildi. Verilerin değerlendirilmesi için SPSS 22 (Statistical Package for Social Sciences) programı kullanıldı. İstatistiksel anlamlılık düzeyi p<0,05 olarak kabul edildi. Sürekli değişkenlerin karşılaştırılmasında t testi, kategorik verilerin karşılaştırılmasında ki-kare testi, sürekli değişkenler arasındaki ilişkileri belirlemek için pearson korelasyon testi kullanıldı. Bulgular Depresyon ve D Tipi kişilik, PMS grubunda kontrol grubuna göre anlamlı olarak daha yaygın bulundu. (p<0.0001). D tipi kişilik ile, PMS ve BDI-21 arasında pozitif korelasyon tespit edildi (r=0,434 p<0.0001,r=0,621 p<0.0001). Sonuç PMS ile depresyon ve D Tipi kişilik arasında pozitif ilişki tespit edildi. Altta yatan mekanizmaları daha iyi anlayabilmek için ileriye dönük, çok hasta sayılı çalışmalar yapılması gerekmektedir.
Premenstruel sendrom ile tip D kişilik ilişkisi
Keywords: Depression; Personality; Premenstrual Syndrome; Depresyon; Kişilik; Premenstruel Sendrom